“Regular la pérdida de la patria potestad por imposibilidad de reinserción familiar a partir de tres años transcurridos desde que inició el acogimiento institucional” - Acaro Arrobo, Lizbeth Marisol (2021)
This research study was conducted by a general objective, which has been complied through a conceptual, doctrinaire and legal study concerning the “Regulation of termination of Parental Rights from three years from institutional care started”, since in our country it has become an evident problem that in care institutions there are big amounts of children and adolescents, staying there three or more years, meanwhile their parents still have Parental Rights over them even if they have no interest in recovering their children. Considering this, it is clearly evident that exists rights violation, specially of the best interest of the child and the right to have a family. During the research development there were conducted theoretical and field study, because of the high quantity of children and adolescents that stay in institutional care for three or more years, observing that care institutions are crammed of children and young, and without solving their familiar and personal conditions; moreover, those minors’ parents demonstrate indifference for their children, so the most reasonable action should be that they lose their parental rights, for this reason our country should regulate and promote an agile process to avoid children rights’ violation, because as it has observed, while these children and adolescents spend time in institutional care and deprived of a family, they can suffer several difficulties as psychological, emotional and social affectations, in consequence, minors start to demonstrate behavioral disorders, which is detrimental for comprehensive development of children. Given these points, to conclude this research study I establish a legal reform project to Código de la Niñez y Adolescencia, with the purpose to include a legal clause that regulates the Termination of Parental Rights on account of the impossibility of family reintegration from three years from institutional care started; because it is demonstrated that parents do not have any interest on recovering their children so as a legal consequence they should lose their Parental Rights, in order those minors can be considered into adoption programs, which should be the best way to guarantee their comprehensive development.